2017
DOI: 10.7874/jao.2017.21.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Combined Therapeutic Effects of Lipoprostaglandin E1 on Sudden Idiopathic Sensorineural Hearing Loss

Abstract: Background and ObjectivesViral and vascular disorders are considered to be a major cause of idiopathic sudden sensorineural hearing loss (ISSNHL). Lipoprostaglandin E1 (lipo-PGE1) has vasodilating activity and has been used to treat ISSNHL. The purpose of this study was to determine the specific therapeutic effects of lipo-PGE1 and compare them to other treatment modalities for ISSNHL.Subjects and MethodsThe study group had 1,052 patients diagnosed with ISSNHL. All were treated with steroid, carbogen inhalatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…In the organ of Corti, the inner hair cells are more vulnerable to ischemia than the outer hair cells [ 39 , 40 ]. As the stria vascularis plays a crucial role in maintaining endocochlear potential, ion transport, and endolymphatic fluid balance essential for ear sensitivity, a cochlea with ischemic injury may lead to hearing loss [ 41 43 ]. Ren et al [ 36 ] reported that hearing function is changed according to clamping and release of the labyrinthine artery in the ischemia-reperfusion model of gerbil cochlea.…”
Section: Discussionmentioning
confidence: 99%
“…In the organ of Corti, the inner hair cells are more vulnerable to ischemia than the outer hair cells [ 39 , 40 ]. As the stria vascularis plays a crucial role in maintaining endocochlear potential, ion transport, and endolymphatic fluid balance essential for ear sensitivity, a cochlea with ischemic injury may lead to hearing loss [ 41 43 ]. Ren et al [ 36 ] reported that hearing function is changed according to clamping and release of the labyrinthine artery in the ischemia-reperfusion model of gerbil cochlea.…”
Section: Discussionmentioning
confidence: 99%
“…La evidencia apunta probablemente hacia una terapia combinada con esteroides 68, por ejemplo, el estudio realizado por Shim y cols, 2017 en el que el uso de lipo prostaglandina E1 asociada con corticoides y oxígeno hiperbárico fue más beneficioso que otras modalidades de tratamiento. 84 Xi y cols, 2020 analizaron el uso de la PGE1 y sus efectos en la agregación plaquetaria, dado que los pacientes con hipoacusia neurosensorial súbita tienen niveles elevados de CD62p y PAC-1, resultando con mejoría en el perfil de la audiometría tonal y disminuyeron los niveles de éstos marcadores. Sugiriendo que el uso de PGE1 podría mejorar la eficacia del tratamiento.…”
Section: Vasoactivos Y Vasodilatadoresunclassified
“…It came to our notice that in our hospital, alprostadil injection has been prescribed in the ENT Outpatient Department to treat some diseases. Furthermore, few articles [4][5][6] have focused on the off label use of alprostadil in ENT patients. In order to understand its utilization patterns a survey of outpatient alprostadil injection prescriptions was performed to provide a prescription audit reference to the pharmacist, and promote the reasonable use of this medicine.…”
Section: Introductionmentioning
confidence: 99%